LPS Impairs Phospholipid Synthesis by Triggering β-Transducin Repeat-containing Protein (β-TrCP)-mediated Polyubiquitination and Degradation of the Surfactant Enzyme Acyl-CoA:Lysophosphatidylcholine Acyltransferase I (LPCAT1) - Zou, Chunbin (American Society for Biochemistry and Molecular Biology, 2011)
Acyl-CoA:lysophosphatidylcholine acyltransferase 1 (LPCAT1) is a relatively newly described and yet indispensable enzyme needed for generation of the bioactive surfactant phospholipid, dipalmitoylphosphatidylcholine (DPPtdCho). Here, we show that lipopolysaccharide (LPS) causes LPCAT1 degradation using the Skp1-Cullin-F-box ubiquitin E3 ligase component, β-transducin repeat-containing protein (β-TrCP), that polyubiquitinates LPCAT1, thereby targeting the enzyme for proteasomal degradation. LPCAT1 was identified as a phosphoenzyme as Ser(178) within a phosphodegron was identified as a putative molecular recognition site for glycogen synthase kinase-3β (GSK-3β) phosphorylation that recruits β-TrCP docking within the enzyme. β-TrCP ubiquitinates LPCAT1 at an acceptor site (Lys(221)), as substitution of Lys(221) with Arg abrogated LPCAT1 polyubiquitination. LPS profoundly reduced immunoreactive LPCAT1 levels and impaired lung surfactant mechanics, effects that were overcome by siRNA to β-TrCP and GSK-3β or LPCAT1 gene transfer, respectively. Thus, LPS appears to destabilize the LPCAT1 protein by GSK-3β-mediated phosphorylation within a canonical phosphodegron for β-TrCP docking and site-specific ubiquitination. LPCAT1 is the first lipogenic substrate for β-TrCP, and the results suggest that modulation of the GSK-3β-SCFβ(TrCP) E3 ligase effector pathway might be a unique strategy to optimize dipalmitoylphosphatidylcholine levels in sepsis.